Primary, Secondary and Tertiary Frequency Control in Dynamic Security Analyses of Electric Power Interconnections - Ivanović, Milan V; Popović, Dragan P.; Minić, Saša (Proceedings, Electrical engineering institute "Nikola Tesla", 2012)
This paper presents the incorporation of primary, secondary and tertiary frequency control in the dynamic security analyses of electric power interconnections. This was done in accordance with the wider environment of the existing state of the Serbian power system. The improved software for dynamic security analysis has been tested on the regional transmission network, which includes power systems of Serbia, Montenegro, Bosnia and Herzegovina, Croatia, Hungary, Macedonia, Romania, Bulgaria, Greece and Albania.
Keywords: Serbian electric power system; dynamic security; frequency; primary; secondary and tertiary control